MELAWAN KETERGANTUNGAN PASAR LEWAT OTENTISITAS KOPI JARINGAN WARKOP NUSANTARA (JWN) - Milki Amirus Sholeh (Journal of Urban Sociology, 2022)
The culture of drinking coffee is not only a consumption activity, but also a reflection of prestige, celebration of consumerism, and ideology. The large consumption of coffee has increased the market share of selling coffee beans or finished products. Coffee is becoming increasingly popular and tends to have price classes and packaging. So far, there is no alternative for someone to brew pure coffee from processed beans directly. This research focuses on the Jaringan Warkop Nusantara (JWN) which initiates the establishment of a supply network starting from coffee beans produced by farmers and sharing free barista training. Other studies refer to the aesthetics of interior design and the concept of traditional coffee culture. So, the research takes the specifications of the JWN organizational group and their working mechanism in concocting quality selected coffee, as well as how to form an educational network for warkop traders so that they can also popularize coffee from pure beans. This research method uses a qualitative approach. The findings of this study indicate that there is an upapa JWN in de-industrialization through coffee consumption activities from warkop. JWN even uses the warkop network as a means of supplying rural coffee farmers who often get less than the maximum selling price.Keywords: Coffee, Jaringan Warkop Nusantara, Dependence, Market, Authenticity